2016
DOI: 10.15835/nbha44110224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc and Bio Fertilizers on Antioxidant Enzymes Activity, Chlorophyll Content, Soluble Sugars and Proline in Triticale Under Salinity Condition

Abstract: In order to study the effects of bio fertilizers and zinc fertilizer on antioxidant enzymes activity, chlorophyll content, soluble sugars and proline in triticale under salinity condition, a factorial experiment was conducted based on randomized complete block design with three replications under greenhouse condition. Experiment factors were included salinity in four levels [no-salt (control or S 0 ), salinity 20 (S 1 ), 40 (S 2 ) and 60 (S 3 ) mM NaCl) equivalent of 1.85, 3.7 and 5.55 dS m −1 respectively], f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 48 publications
8
13
0
Order By: Relevance
“…Zn ions bind to ligands containing sulfur, nitrogen, and to a lesser extent oxygen, and preferentially bind to the membrane proteins. 28 Our results are in agreement with the findings of Tavallali et al 37 who reported that Zn is able to facilitate the biosynthesis of antioxidant enzymes and enhance antioxidant activity in the leaves of pistachio under abiotic stress conditions. The balance between the generation and removal of free radicals determines the survival of the system.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Zn ions bind to ligands containing sulfur, nitrogen, and to a lesser extent oxygen, and preferentially bind to the membrane proteins. 28 Our results are in agreement with the findings of Tavallali et al 37 who reported that Zn is able to facilitate the biosynthesis of antioxidant enzymes and enhance antioxidant activity in the leaves of pistachio under abiotic stress conditions. The balance between the generation and removal of free radicals determines the survival of the system.…”
Section: Discussionsupporting
confidence: 93%
“…25 Another reason for the decline in chlorophyll is the application of a glutamate precursor for the biosynthesis of proline. 26 Enhancing chlorophylls content by ZnO-NPs treatment are in agreement with the results obtained by Fathi et al 27 and Kheirizadeh Arough et al 28 who mentioned that ZnO-NPs treated plants showed higher amount of total chlorophyll content than the control. Moreover, Sharma et al 29 reported that Zn treatment increased the growth of cabbage and improved the chlorophyll content and photosynthetic activity in the leaves.…”
Section: Discussionsupporting
confidence: 85%
“…Plants augment the antioxidant systems including both non-enzymatic and enzymatic antioxidants such as the POD and PPO in order to cope with the ROS. 31 The results regarding the enhanced PPO and POD activities by ZnO-NPs are in conformity with the findings of Kheirizadeh Arough et al 32 who found that 0.4 and 0.8 g L -1 ZnO-NPs significantly increased the activities of antioxidant enzymes such as PPO and POD in Triticale plants under abiotic stress.…”
Section: Discussionsupporting
confidence: 87%
“…increased the growth and biomass of canola plants by regulating the oxidative stress enzymes and essential nutrient under water deficit. Kheirizadeh Arough et al (2016) suggested that the positive effects of zinc application under salt stress are included protecting chlorophyll against free radicals, removing the reactive oxygen species, increasing of CAT and PPO activity.…”
Section: Treatmentmentioning
confidence: 99%
“…Also, means comparison between salinity and nano oxide showed that the highest grain yield (2.59 g per plant) was obtained in nano oxide as N 4 in no salinity stress (Table 5). Kheirizadeh Arough et al (2016) showed that salinity stress negatively affected growth, yield, antioxidant enzymes and ions accumulation in barley plants; however, some of these changes could be compensated by the nano oxide foliar application. Such effects of foliar application with micronutrients (Zn and Fe) might be due to their critical role in crop growth, involving in photosynthesis processes and other biochemical and physiological activates and thus their importance in achieving higher yields.…”
Section: Grain Yieldmentioning
confidence: 99%